Copolyesters made from 3-hydroxybutyric acid and their manufacturing method

A copolyester of 3-hydroxybutyric acid and hydroxyalkanoic acid with controlled content and chain length addresses biodegradability and thermal stability issues in PHA, achieving high biodegradability and mechanical strength.

JP7620957B2Active Publication Date: 2025-01-24DIC CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024536081
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-01
Filing Date
2023-07-31
Publication Date
2025-01-24
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

Existing biodegradable polymers like PHA require genetic manipulation and have issues with thermal decomposition, leading to unpleasant odors and hydrolysis, and the effect of 3HB chain length on biodegradability is unclear, especially at ratios below 50%.

Method used

A copolyester composed of 3-hydroxybutyric acid and hydroxyalkanoic acid with a specific content (1 to 40 mol%) and average chain length (2 to 20) is developed, optimizing biodegradability and mechanical properties.

Benefits of technology

The copolyester exhibits high biodegradability and balanced mechanical properties, suppressing thermal decomposition products and maintaining structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620957000005
    Figure 0007620957000005
  • Figure 0007620957000006
    Figure 0007620957000006
  • Figure 0007620957000001
    Figure 0007620957000001
Patent Text Reader

Abstract

The present invention provides a copolyester comprising 3-hydroxybutyric acid and exhibiting high biodegradability, and a method for producing said copolyester. A copolyester according to the present invention is a copolyester of 3-hydroxybutyric acid (3HB) and hydroxyalkanoic acid (HA), the copolyester having structural units (3HB-U) derived from 3-hydroxybutyric acid (3HB) and structural units (HA-U) derived from hydroxyalkanoic acid (HA). The content of the structural units (3HB-U) derived from 3-hydroxybutyric acid (3HB) is 1 to 40 mol% relative to 100 mol of all the structural units of the copolyester, and the average chain length of the structural units (3HB-U) derived from 3-hydroxybutyric acid (3HB) in the copolyester is 2 to 20.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copolyester made of 3-hydroxybutyric acid and a method for producing the same. This application claims priority based on Japanese Patent Application No. 2022-122989, filed on August 1, 2022, the contents of which are incorporated herein by reference. [Background technology]

[0002] In response to the social issue of environmental degradation caused by the mass waste of plastic, there is a growing demand for sustainable products (packaging materials, films) made from resins that are biodegradable in all conditions (seawater, freshwater, soil, compost). Polyhydroxyalkanoates (PHAs) produced by bacteria are examples of resins that are biodegradable under all of the above-mentioned environments. However, controlling the structure of PHA requires genetic manipulation of bacteria, and developing resins with the desired physical properties requires a great deal of time and effort. When PHA is synthesized from the corresponding monomer by chemical polymerization, the degree of freedom in the resin structure is high, but the monomer, which is the main structural unit of PHA, is susceptible to thermal decomposition, which generates carboxylic acid-based decomposition products, and there are issues with the generation of unpleasant odors and susceptibility to hydrolysis. Therefore, PHA-based synthetic resins with reduced amounts of decomposition products are required. Patent Document 1 discloses a copolymer resin composition containing a biodegradable copolyester of 3-hydroxybutyric acid, 3-hydroxyvaleric acid, and lactic acid, the copolyester containing 10 to 25 mol % of 3-hydroxybutyric acid units relative to all constituent units. Non-Patent Document 1 discloses a biodegradable copolyester consisting of 3-hydroxybutyric acid and lactic acid, in which the content of 3-hydroxybutyric acid units relative to all constituent units is 50 to 78% and the average sequence length of 3-hydroxybutyric acid is 2.7 to 22.3. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-87207 A [Non-patent literature]

[0004] [Non-Patent Document 1] Yuta Tabata, Hideki Abe, “Effects of composition and sequential structure on thermal properties for copolymer of 3-hydroxybutyrate and lactate units”, Polymer Degradation and Stability,98 (2013) 1796-1803. Summary of the Invention [Problem to be solved by the invention]

[0005] However, Patent Document 1 and Non-Patent Document 1 do not clearly state the effects of the content of 3-hydroxybutyric acid units relative to all constituent units (hereinafter also referred to as the "3HB content") and the average chain length of 3-hydroxybutyric acid (hereinafter also referred to as the "3HB chain length") on biodegradability, and it was not possible to predict whether biodegradability would occur, particularly when the 3HB ratio was 50% or less.

[0006] The present invention has been made to solve the above-mentioned problems, and aims to provide a copolyester made of 3-hydroxybutyric acid (hereinafter, also referred to as "3HB copolyester") that exhibits high biodegradability at a specific 3HB ratio and 3HB chain length, and a method for producing the same. [Means for solving the problem]

[0007] The present disclosure includes the following embodiments [1] to [8]. [1] The copolyester has a structural unit (3HB-U) derived from 3-hydroxybutyric acid (3HB) and a structural unit (HA-U) derived from hydroxyalkanoic acid (HA), the content of the structural unit (3HB-U) derived from 3-hydroxybutyric acid (3HB) is 1 to 40 mol% relative to 100 mol of all structural units of the copolyester, The copolyester is characterized in that the average sequence length of the structural units (3HB-U) derived from 3-hydroxybutyric acid (3HB) in the copolyester is 2 to 20. [2] The copolyester according to [1], which is a reaction product of poly(3-hydroxybutyric acid) (PHB) with the hydroxyalkanoic acid (HA) or a polyester (PHA) of the hydroxyalkanoic acid (HA). [3] The copolyester according to [2], wherein the poly(3-hydroxybutyric acid) (PHB) has a number average molecular weight of 1,000 to 500,000. [4] The copolyester according to [2] or [3], wherein the polyester (PHA) of the hydroxyalkanoic acid (HA) has a number average molecular weight of 1,000 to 500,000. [5] The copolyester according to any one of [1] to [4], wherein the hydroxyalkanoic acid (HA) is lactic acid. [6] A method for producing the copolyester according to any one of [1] to [5], comprising the steps of: A method for producing a copolyester, comprising the step of reacting poly(3-hydroxybutyric acid) (PHB), which is a polyester of 3-hydroxybutyric acid (3HB), with the hydroxyalkanoic acid (HA) or a polyester of hydroxyalkanoic acid (HA) (PHA). [7] A resin composition comprising the copolyester according to any one of [1] to [5]. [8] A sheet or film made of the resin composition described in [7]. Effect of the Invention

[0008] An object of the present invention is to provide a copolyester made of 3-hydroxybutyric acid that exhibits high biodegradability, and a method for producing the same. [Brief description of the drawings]

[0009] [Figure 1] 1 is a 1H-NMR spectrum of the copolyester of Example 1 of the present invention. [Diagram 2] 1 is a 13C-NMR spectrum of the copolyester of Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in more detail below. Note that the present invention is not limited to the following embodiments.

[0011] "~" means greater than or equal to the value before the "~", and less than or equal to the value after the "~".

[0012] (Copolyester) A copolyester according to one embodiment of the present invention (copolyester according to the present embodiment) is a copolyester of 3-hydroxybutyric acid (3HB) and hydroxyalkanoic acid (HA) (sometimes referred to as HB-HA copolyester). The copolyester according to the present embodiment has a structural unit (3HB-U) derived from the 3-hydroxybutyric acid (3HB) and a structural unit (HA-U) derived from the hydroxyalkanoic acid (HA). The content of the structural unit (3HB-U) derived from the 3-hydroxybutyric acid (3HB) is 1 to 40 mol% relative to 100 mol of all structural units of the copolyester. The average sequence length of the structural unit (3HB-U) derived from the 3-hydroxybutyric acid (3HB) in the copolyester is 2 to 20.

[0013] The structural unit (3HB-U) derived from 3-hydroxybutyric acid (3HB) means one residue of 3-hydroxybutyric acid in the copolymer, specifically, a structure in which the hydrogen atom in the hydroxy group and the hydroxy residue in the carboxyl group of 3-hydroxybutyric acid have been removed. The structural unit (HA-U) derived from hydroxyalkanoic acid (HA) means one residue of hydroxyalkanoic acid in the copolymer, specifically, the structure obtained by removing the hydrogen atom in the hydroxy group and the hydroxy residue in the carboxyl group of the hydroxyalkanoic acid.

[0014] The total number of moles of the constituent units of the copolyester means the total number of moles of the constituent units derived from all the monomers constituting the copolyester. In addition, when the copolyester of the present embodiment has the constituent unit (3HB-U) derived from the 3-hydroxybutyric acid (3HB) and the constituent unit (HA-U) derived from the hydroxyalkanoic acid (HA), and does not contain any other constituent units, the total number of moles of the constituent unit (3HB-U) derived from the 3-hydroxybutyric acid (3HB) and the constituent unit (HA-U) derived from the hydroxyalkanoic acid (HA) is the total number of moles of the constituent unit (3HB-U) derived from the 3-hydroxybutyric acid (3HB) and the constituent unit (HA-U) derived from the hydroxyalkanoic acid (HA). The content (mol %) of the structural unit (3HB-U) derived from 3-hydroxybutyric acid (3HB) is the percentage of the number of moles of the structural unit (3HB-U) derived from 3-hydroxybutyric acid (3HB) relative to the total number of moles of the structural units derived from all monomers that constitute the copolyester.

[0015] The chain structure of a structural unit derived from 3-hydroxybutyric acid (3HB-U) means a structure in which one residue of 3-hydroxybutyric acid is consecutively ester-bonded; specifically, it means a structure in which the structure in which the hydrogen atom in the hydroxy group of 3-hydroxybutyric acid and the hydroxy residue in the carboxyl group are removed are consecutively ester-bonded. The average sequence length of the structural unit derived from 3-hydroxybutyric acid (3HB-U) is the average number of consecutive structural units derived from 3-hydroxybutyric acid that appear in a sequence in one polyester molecule. The method for evaluating this will be described in the Examples below.

[0016] The copolyester of the present embodiment is preferably a reaction product of the poly(3-hydroxybutyric acid) (PHB) and the hydroxyalkanoic acid (HA) or a polyester of the hydroxyalkanoic acid (HA) (PHA). Polyester (PHB) of 3-hydroxybutyric acid (3HB) is a polyester in which structural units derived from 3-hydroxybutyric acid are successively ester-linked. Specifically, it is a polyester in which the structure in which the hydrogen atoms in the hydroxyl groups of 3-hydroxybutyric acid and the hydroxyl residues in the carboxyl groups are removed are successively ester-linked. Polyester of hydroxyalkanoic acid (HA) (PHA) is a polyester in which structural units derived from hydroxyalkanoic acid (HA) are successively ester-linked. Specifically, it is a polyester in which the structure resulting from removing the hydrogen atoms in the hydroxyl groups of hydroxyalkanoic acid (HA) and the hydroxyl residues in the carboxyl groups is successively ester-linked.

[0017] Although not particularly limited, suitable examples of the copolyester of the present embodiment include those represented by the following formulae (1) to (3).

[0018] [ka] (In formula (1), o, p, and q each independently represent a positive integer.)

[0019] [ka] (In formula (2), o, p, and q each independently represent a positive integer.)

[0020] [ka] (In formula (3), o, p, and q each independently represent a positive integer.)

[0021] <3-hydroxybutyric acid (3HB) and building blocks derived from 3HB (3HB-U)> The content of the structural unit (3HB-U) derived from 3-hydroxybutyric acid (3HB) according to this embodiment is 1 to 40 mol%, preferably 2 to 30 mol%, more preferably 3 to 25 mol%, and even more preferably 4 to 20 mol% relative to 100 mol of all structural units of the copolyester of this embodiment. Any combination of these upper and lower limits can be used. If the structural unit (3HB-U) is less than 1 mol%, the biodegradability of the copolyester decreases. If the structural unit (3HB-U) is more than 40 mol%, acidic decomposition products of 3-hydroxybutyric acid are easily generated, which can cause problems such as unpleasant odors and increased susceptibility to hydrolysis.

[0022] The average sequence length of the 3-hydroxybutyric acid-derived structural unit (3HB-U) in the copolyester of this embodiment is 2 to 20, preferably 3 to 15, more preferably 4 to 10, and even more preferably 5 to 8. Any combination of these upper and lower limits can be used. When the average sequence length of the structural unit (3HB-U) is less than 2, not only the biodegradability of the copolyester but also the mechanical properties and melting point are reduced. When the average sequence length of the structural unit (3HB-U) exceeds 20, the biodegradability of the copolyester is reduced.

[0023] It is particularly preferred that the content of the 3-hydroxybutyric acid (3HB-U)-derived structural units of this embodiment is 4 to 20 mol % relative to 100 mol of all structural units of the copolyester of this embodiment, and that the average sequence length of the 3-hydroxybutyric acid-derived structural units (3HB-U) in the copolyester of this embodiment is 5 to 8, since this can achieve high biodegradability, mechanical properties, and melting point while also inhibiting the decomposition of 3-hydroxybutyric acid.

[0024] The content of the structural unit (3HB-U) derived from 3-hydroxybutyric acid (3HB) in the copolyester of the present embodiment is 1The content of the structural unit (3HB-U) can be adjusted by the amount of 3-hydroxybutyric acid (3HB) added in the raw material (or raw material of the intermediate product) for producing the copolyester in the production method of the copolyester of the present embodiment described later.

[0025] The average sequence length of the structural unit (3HB-U) derived from 3-hydroxybutyric acid in the copolyester of this embodiment is 1 H-NMR, 13 It can be measured by C-NMR spectrum, and in detail, it can be measured by the method described in the examples below. The average chain length of the structural unit (3HB-U) can be adjusted by controlling (for example, block polymerization, etc.) the esterification reaction between 3-hydroxybutyric acid and esterification reaction between 3-hydroxybutyric acid and hydroxyalkanoic acid in the production method of the copolyester of this embodiment described below. For example, a method of controlling the order of charging each raw material, a method of adjusting the speed of each reaction, etc. can be mentioned. For example, a method of first obtaining an oligomer or polyester (PHB) of 3-hydroxybutyric acid (3HB) and then charging a hydroxyalkanoic acid (HA); a method of first obtaining an oligomer or polyester (PHB) of 3-hydroxybutyric acid (3HB), obtaining a polyester (PHA) of hydroxyalkanoic acid (HA), and then reacting the obtained polyester (PHB) with the polyester (PHA). The 3-hydroxybutyric acid of the present invention may be any of the racemic, (R) and (S) forms. It is particularly preferable to use the (R) form since it has high biodegradability, mechanical properties and melting point.

[0026] <Hydroxyalkanoic acid (HA), structural unit derived from HA (HA-U)> Examples of the hydroxyalkanoic acid (HA) according to the present embodiment include C alkanoic acids such as glycolic acid, 2-hydroxypropanoic acid (lactic acid), 3-hydroxypropanoic acid, 2-hydroxybutanoic acid (2-hydroxybutyric acid), 4-hydroxybutanoic acid, 3-hydroxy-3-methyl-butanoic acid, 2-hydroxypentanoic acid (2-hydroxyvaleric acid), 3-hydroxypentanoic acid, 5-hydroxypentanoic acid, 2-hydroxy-2-methyl-pentanoic acid, 3-hydroxyhexanoic acid, 6-hydroxyhexanoic acid, 6-hydroxyheptanoic acid, 3-hydroxyheptanoic acid, 7-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 8-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 9-hydroxynonanoic acid, 3-hydroxydecanoic acid, and 10-hydroxydecanoic acid. 1-6 Hydroxy C, optionally having an alkyl group 2-15 Examples include alkanoic acid, 12-hydroxystearic acid, and ricinoleic acid.

[0027] The hydroxyalkanoic acid (HA) may be a corresponding lactone. Examples of lactones include di-C lactones such as β-propiolactone, β-dimethylpropiolactone, γ-butyrolactone, γ-dimethylbutyrolactone, δ-valerolactone, and ε-caprolactone. 1-12 C which may have an alkyl group 3-15 Lactones, etc.

[0028] These hydroxyalkanoic acids and lactones can be used alone or in combination of two or more. Among these hydroxyalkanoic acids, hydroxyalkanoic acids such as 3-hydroxypropanoic acid, 4-hydroxybutanoic acid, 3-hydroxyvaleric acid, 3-hydroxyhexanoic acid, 6-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 3-hydroxynonanoic acid, and 3-hydroxydecanoic acid are preferred from the viewpoint of biodegradability. 3-10 Alkanoic acid (hydroxy C other than 3-hydroxybutyric acid) 3-10 Alkanoic acid units) or the corresponding lactones are preferred. The hydroxyalkanoic acid (HA) according to the present embodiment is preferably 2-hydroxypropanoic acid (lactic acid). That is, the structure (HA-U) derived from the hydroxyalkanoic acid (HA) according to the present embodiment is preferably a structure derived from 2-hydroxypropanoic acid (lactic acid).

[0029] <Other hydroxycarboxylic acid units> In the copolyester of the present embodiment, in addition to the above-mentioned 3HB-derived structural unit (3HB-U) and hydroxyalkanoic acid (HA)-derived structural unit (HA-U), other structural units may be included, such as units (HCA-U) derived from hydroxycarboxylic acids (HCAs) other than 3-hydroxybutyric acid and hydroxyalkanoic acids (HA) (other hydroxycarboxylic acid units containing lactone units). When the copolyester of this embodiment contains other structural units in addition to the structural unit (3HB-U) derived from 3HB and the structural unit (HA-U) derived from hydroxyalkanoic acid (HA), the molar content of the other structural units is preferably 50 mol% or less, more preferably 30 mol% or less, and even more preferably 20 mol% or less, relative to 100 mol of all structural units of the copolyester of this embodiment. Furthermore, the molar content of the other structural units may be 5 mol% or more, relative to 100 mol of all structural units of the copolyester of this embodiment. Examples of other hydroxycarboxylic acid units include units of hydroxycycloalkanecarboxylic acid (such as hydroxycyclohexanecarboxylic acid), hydroxybenzoic acid (such as hydroxyarenecarboxylic acid), etc. These hydroxycarboxylic acid units can be used alone or in combination of two or more kinds.

[0030] <Copolyester Structure and Properties> The copolyester of the present embodiment is a copolyester of 3-hydroxybutyric acid (3HB) and a hydroxyalkanoic acid (HA), and is preferably a reaction product of the poly(3-hydroxybutyric acid) (PHB) and the hydroxyalkanoic acid (HA) or a polyester (PHA) of the hydroxyalkanoic acid (HA). In the copolyester of this embodiment, it is preferable that the content of the structural unit (HB-U) derived from 3-hydroxybutyric acid (3HB) is 1 to 40 mol% relative to 100 mol of all structural units of the copolyester, and the average sequence length of the 3-hydroxybutyric acid units in the copolyester is 2 to 20. It is more preferable that the content of the structural unit (HB-U) derived from 3-hydroxybutyric acid (3HB) is 2 to 30 mol% relative to 100 mol of all structural units of the copolyester, and the average sequence length of the 3-hydroxybutyric acid units in the copolyester is 3 to 15. It is even more preferable that the content of the structural unit (HB-U) derived from 3-hydroxybutyric acid (3HB) is 4 to 20 mol% relative to 100 mol of all structural units of the copolyester, and the average sequence length of the 3-hydroxybutyric acid units in the copolyester is 5 to 8.

[0031] The weight average molecular weight (Mw) of the copolyester of this embodiment, as measured by gel permeation chromatography (GPC), may be, in terms of polystyrene, a lower limit of 5,000 or more, 6,000 or more, 7,000 or more, 8,000 or more, or 10,000 or more, and an upper limit of 1,000,000 or less, 500,000 or less, 100,000 or less, 50,000 or less, or 30,000 or less. Any combination of these upper and lower limits may be used. If the number average molecular weight (Mn) of the copolyester is 1,000,000 or more, molding processing becomes difficult. Also, if the number average molecular weight (Mn) of the copolyester is 5,000 or less, it does not exhibit sufficient mechanical properties.

[0032] The copolyester of the present embodiment has the above structure, which improves biodegradability, and therefore has both biodegradability and mechanical properties at a high level. In addition, the above preferred structural range of the copolyester of the present embodiment can be appropriately selected depending on the application. For example, the biodegradability can be easily adjusted by adjusting the content of the structural unit derived from 3-hydroxybutyric acid.

[0033] <Poly(3-hydroxybutyrate) (PHB)> The poly(3-hydroxybutyric acid) (PHB) according to the present embodiment is preferably a poly(3-hydroxybutyric acid) obtained by esterification of 3-hydroxybutyric acid (3HB) with itself. The poly(3-hydroxybutyric acid) (PHB) according to the present embodiment includes a poly(3-hydroxybutyric acid) structure obtained by esterification of 3-hydroxybutyric acid (3HB) with itself.

[0034] The method for producing poly(3-hydroxybutyric acid) is not particularly limited, and examples thereof include a method similar to the method for producing polylactic acid described in Non-Patent Document A below. [Non-patent Document A] Shinji Yamada, Aknori Takasu, Sadatsugu Takayama, Kazuhiko Kawamura, Microwave-assisted solution polycondensation of L-lactic acid using a Dean-Stark apparatus for a non-thermal microwave polymerization effect induced by the electric field, Polym. Chem., 5(2014)5283-5288. A specific example of such a method is to add an acid catalyst such as p-toluenesulfonic acid to 3-hydroxybutyric acid and carry out a dehydration esterification reaction in a solvent such as toluene at a temperature of 80 to 150°C.

[0035] The number average molecular weight (Mn) of poly(3-hydroxybutyric acid) (PHB) may be 1,000 or more, 2,000 or more, 4,000 or more, 8,000 or more, or 10,000 or more, and may be 1,000,000 or less, 500,000 or less, 100,000 or less, 50,000 or less, or 10,000 or less. Any combination of these upper and lower limits may be used. When the number average molecular weight (Mn) of poly(3-hydroxybutyric acid) (PHB) is 1,000,000 or more, the reaction with the hydroxyalkanoic acid (HA) or the polyester (PHA) of the former hydroxyalkanoic acid (HA) becomes extremely difficult. Furthermore, when the number average molecular weight (Mn) of poly(3-hydroxybutyric acid) (PHB) is 1,000 or less, it becomes difficult to control the chain length in the reaction with the hydroxyalkanoic acid (HA) or the polyester (PHA) of the former hydroxyalkanoic acid (HA).

[0036] The reaction may be carried out in the absence or presence of a catalyst, such as a metal catalyst, a base catalyst, a phosphine catalyst, or an acid catalyst. Examples of the metal catalyst include metal compounds containing alkali metals (such as sodium), alkaline earth metals (such as magnesium, calcium, barium, etc.), transition metals (such as manganese, zinc, cadmium, lead, cobalt, titanium, etc.), metals in Group 13 of the periodic table (such as aluminum), metals in Group 14 of the periodic table (such as germanium, tin), and metals in Group 15 of the periodic table (such as antimony). Examples of the base catalyst include tertiary amines (trialkylamines such as trimethylamine and triethylamine, quaternary ammonium salts (tetraalkylammonium halides such as tetraethylammonium chloride and tetraethylammonium bromide, benzyltrialkylammonium halides such as benzyltrimethylammonium chloride, etc.)). Examples of the phosphine catalyst include trialkylphosphines (trimethylphosphine, triethylphosphine, tri-n-butylphosphine, tri-tert-butylphosphine, tricyclohexylphosphine, etc.), triarylphosphines (triphenylphosphine, tri(o-tolyl)phosphine, etc.), and the like. Examples of the acid catalyst include inorganic acids (e.g., sulfuric acid, hydrogen chloride (or hydrochloric acid), nitric acid, phosphoric acid, etc.), organic acids (e.g., sulfonic acids (alkanesulfonic acids such as methanesulfonic acid, ethanesulfonic acid, trifluoromethanesulfonic acid, etc., arenesulfonic acids such as p-toluenesulfonic acid, etc.) and the like. Examples of the metal compound include organic acid salts (acetates, propionates, etc.), inorganic acid salts (borates, carbonates, etc.), metal oxides (germanium oxide, etc.), metal chlorides (tin chloride, etc.), metal alkoxides (titanium tetraalkoxide, titanium tetra t-butoxide, aluminum isopropoxide, zinc t-butoxide, potassium t-butoxide, etc.), alkyl metals (trialkylaluminum, etc.). These catalysts may be used alone or in combination. The use of an acid catalyst is preferred from the viewpoint of increasing the activity of the esterification reaction, and arenesulfonic acids such as p-toluenesulfonic acid are preferred from the viewpoints of stability in handling and activity as a catalyst.

[0037] The amount of the catalyst used is usually in the range of 0.001 to 5.0% by mass based on the mass of 3-hydroxybutyric acid (3HB).

[0038] The reaction may be carried out in the presence or absence of a solvent. Examples of the solvent include hydrocarbons (aliphatic hydrocarbons such as hexane, octane, and cyclohexane, and aromatic hydrocarbons such as toluene, xylene mesitylene, tetralin, chlorobenzene, o-dichlorobenzene, and 1,2,4-trichlorobenzene), halogenated hydrocarbons (dichloromethane, chloroform, carbon tetrachloride, dichloroethane, and the like), ethers (dioxane, tetrahydrofuran, diphenyl ether, and the like), ketones (acetone, methyl ethyl ketone, and the like), esters (methyl acetate, ethyl acetate, butyl acetate, and the like), amides (dimethylformamide, diethylformamide, dimethylacetamide, diethylacetamide, N-methylpyrrolidone, and the like), sulfoxides (dimethyl sulfoxide, and the like), and cellosolve acetates (C such as ethyl cellosolve acetate, and the like). 1-4 Alkyl cellosolve acetate, etc. These solvents can be used alone or in combination of two or more.

[0039] The reaction atmosphere may be air or an inert gas (nitrogen, helium, etc.) atmosphere, and the reaction pressure may be normal pressure or reduced pressure. The reaction can be easily progressed by distilling water generated in the esterification reaction out of the reaction system.

[0040] The method for producing the polyester (PHA) of hydroxyalkanoic acid (HA) is not particularly limited, and may be the same method as the method for producing polylactic acid described in Non-Patent Document A above. For example, a method in which a sulfonic acid such as p-toluenesulfonic acid is added to a hydroxyalkanoic acid and a dehydration esterification reaction is carried out at a temperature of 80 to 160° C. in a solvent such as toluene can be mentioned.

[0041] The number average molecular weight (Mn) of the polyester (PHA) of hydroxyalkanoic acid (HA) may be 1,000 or more, 2,000 or more, 4,000 or more, 8,000 or more, or 10,000 or more, and the upper limit may be 1,000,000 or less, 500,000 or less, 100,000 or less, 50,000 or less, or 10,000 or less. Any combination of these upper and lower limits may be used. When the number average molecular weight (Mn) of the polyester (PHA) is 1,000,000 or less, the reaction with poly(3-hydroxybutyric acid) (PHB) is easily promoted. In addition, when the number average molecular weight (Mn) of the polyester (PHA) is 1,000 or more, the molecular weight and chain length of the copolyester of this embodiment can be easily controlled in the reaction with the poly(3-hydroxybutyric acid) (PHB).

[0042] (Production method of copolyester) The method for producing the copolyester of this embodiment (sometimes simply referred to as the production method of this embodiment) is the method for producing the copolyester of this embodiment described above. The production method of this embodiment includes a step of reacting poly(3-hydroxybutyric acid) (PHB) with the hydroxyalkanoic acid (HA) or a polyester (PHA) of the hydroxyalkanoic acid (HA). The manufacturing method of this embodiment preferably includes the following first and second steps. The first step is a step of subjecting the 3-hydroxybutyric acid to an esterification reaction to obtain the poly(3-hydroxybutyric acid) (PHB); The second step is a step of reacting the poly(3-hydroxybutyric acid) (PHB) obtained in the first step with the hydroxyalkanoic acid (HA) or a polyester (PHA) of the hydroxyalkanoic acid (HA).

[0043] In addition, when the polyester (PHA) of hydroxyalkanoic acid (HA) is used in the second step, it is preferable to further include the following step 1A before the second step. Step 1A: A step of subjecting the hydroxyalkanoic acids (HA) to an esterification reaction with each other to obtain a polyester (PHA) of the hydroxyalkanoic acid (HA).

[0044] The manufacturing method of this embodiment may be, for example, a method in which a mixed solution containing poly(3-hydroxybutyric acid) (PHB) and the hydroxyalkanoic acid (HA) or a polyester (PHA) of the hydroxyalkanoic acid (HA) is subjected to an ester exchange reaction to obtain the copolyester of this embodiment. Examples of the ester exchange reaction include the method described in Non-Patent Document 1. The method for producing the copolyester of the present embodiment may be, for example, a method in which a mixture containing poly(3-hydroxybutyric acid) (PHB) and a polyester (PHA) of hydroxyalkanoic acid (HA) such as lactic acid or polylactic acid is subjected to an ester exchange reaction to obtain the copolyester of the present embodiment. The temperature of the ester exchange reaction is preferably, for example, 90 to 200°C.

[0045] When the production method of the present embodiment uses an ester exchange reaction between poly(3-hydroxybutyric acid) (PHB) and the polyester (PHA) of the hydroxyalkanoic acid (HA), the molar ratio of the polyester (PHB) and the polyester (PHA) is not particularly limited as long as the content of the structural unit (3HB-U) of 3-hydroxybutyric acid (3HB) in the produced copolyester of the present embodiment and the average chain length of the structural unit of 3-hydroxybutyric acid (3HB) are within the above-mentioned range. For example, the molar ratio of the structural unit (3HB-U) derived from polyester (PHB) and the structural unit (HA-U) derived from polyester (PHA) is 1 to 40 mol%, preferably 2 to 30 mol%, more preferably 3 to 25 mol%, and even more preferably 4 to 20 mol%. When the molar ratio of the constituent unit (3HB-U) derived from poly(3-hydroxybutyric acid) (PHB) to the constituent unit (HA-U) derived from polyester (PHA) exceeds 40 mol%, acidic decomposition products of 3-hydroxybutyric acid are likely to be generated, which may cause problems such as unpleasant odors and susceptibility to hydrolysis. When the molar ratio of the constituent unit (3HB-U) derived from polyester (PHB) to the constituent unit (HA-U) derived from polyester (PHA) is less than 1, the biodegradability of the copolyester decreases.

[0046] The catalyst used in the transesterification reaction is preferably a titanium catalyst. Examples of the titanium catalyst include titanium tetramethoxide, titanium tetraethoxide, titanium tetraisopropoxide, titanium tetra n-propoxide, titanium tetra n-butoxide, tetrakis(2-ethylhexyloxy)titanium, and tetrastearyloxytitanium. In terms of stability in handling and activity as a catalyst, titanium tetraisopropoxide is preferred.

[0047] The amount of the catalyst used is usually in the range of 0.001 to 5.0% by mass based on the total mass of poly(3-hydroxybutyric acid) (PHB) and the hydroxyalkanoic acid (HA) or the polyester (PHA) of the hydroxyalkanoic acid (HA). The reaction atmosphere may be air or an inert gas (nitrogen, helium, etc.) atmosphere, and the reaction pressure may be normal pressure or reduced pressure.

[0048] The reaction is carried out until the average sequence length of the structural units (3HB-U) derived from 3-hydroxybutyric acid (3HB) reaches 2 to 20. The reaction temperature is usually 80 to 250° C., preferably 100 to 200° C., more preferably 110 to 160° C., and even more preferably 125 to 150° C. The reaction time is usually 1 minute to 200 hours, preferably 5 minutes to 100 hours, more preferably 10 minutes to 80 hours, and even more preferably 15 minutes to 60 hours.

[0049] In the production method of the present embodiment, the transesterification reaction and the esterification reaction can be carried out simultaneously. By carrying out the transesterification reaction and the esterification reaction simultaneously, the control of the chain length by the transesterification reaction and the polymerization growth by the esterification reaction can be carried out simultaneously.

[0050] (Polyurethane) An application example of the copolyester of this embodiment includes, for example, a polyurethane derived from the copolyester of this embodiment (sometimes referred to as "polyurethane according to this embodiment") obtained using the copolyester of this embodiment. The polyurethane according to the present embodiment can be obtained, for example, by reacting the copolyester according to the present embodiment with a polyisocyanate. If necessary, a polyol other than the copolyester according to the present embodiment, a chain extender, a chain terminator, or a crosslinking agent may be used in combination. The copolyester according to the present embodiment for obtaining the polyurethane is preferably a polyester polyol. Specifically, the polyurethane according to this embodiment is obtained by reacting a polyol with a polyisocyanate, and at least the copolyester according to this embodiment is used as the polyol. Thus, the polyurethane is a reaction product obtained by reacting a polyol with a polyisocyanate, and the polyurethane has structural units derived from the polyol and structural units derived from the polyisocyanate, and at least structural units derived from the copolyester according to this embodiment.

[0051] Examples of the chain extender include aliphatic polyol compounds such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, hexamethylene glycol, saccharose, methylene glycol, glycerin, sorbitol, and neopentyl glycol; aromatic polyol compounds such as bisphenol A, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl sulfone, hydrogenated bisphenol A, and hydroquinone; Examples of the chain extenders include aliphatic polyol compounds; water; and amine compounds such as ethylenediamine, 1,2-propanediamine, 1,6-hexamethylenediamine, piperazine, 2-methylpiperazine, 2,5-dimethylpiperazine, isophoronediamine, 4,4'-dicyclohexylmethanediamine, 3,3'-dimethyl-4,4'-dicyclohexylmethanediamine, 1,2-cyclohexanediamine, 1,4-cyclohexanediamine, aminoethylethanolamine, hydrazine, diethylenetriamine, and triethylenetetramine. These chain extenders may be used alone or in combination of two or more. Among these, aliphatic polyol compounds are preferred, and neopentyl glycol is more preferred.

[0052] The content of the copolyester of the present embodiment in 100% by mass of all polyols used in the polyurethane synthesis is preferably 10 to 100% by mass, and more preferably 50 to 100% by mass.

[0053] Examples of polyisocyanates include 1,3- and 1,4-phenylene diisocyanate, 1-methyl-2,4-phenylene diisocyanate, 1-methyl-2,6-phenylene diisocyanate, 1-methyl-2,5-phenylene diisocyanate, 1-methyl-2,6-phenylene diisocyanate, 1-methyl-3,5-phenylene diisocyanate, 1-ethyl-2,4-phenylene diisocyanate, 1-isopropyl-2,4 -phenylene diisocyanate, 1,3-dimethyl-2,4-phenylene diisocyanate, 1,3-dimethyl-4,6-phenylene diisocyanate, 1,4-dimethyl-2,5-phenylene diisocyanate, diethylbenzene diisocyanate, diisopropylbenzene diisocyanate, 1-methyl-3,5-diethylbenzene diisocyanate, 3-methyl-1,5-diethylbenzene-2,4-diisocyanate, 1,3,5- Triethylbenzene-2,4-diisocyanate, naphthalene-1,4-diisocyanate, naphthalene-1,5-diisocyanate, 1-methyl-naphthalene-1,5-diisocyanate, naphthalene-2,6-diisocyanate, naphthalene-2,7-diisocyanate, 1,1-dinaphthyl-2,2'-diisocyanate, biphenyl-2,4'-diisocyanate, biphenyl-4,4'-diisocyanate, 3-3'-dimethylbiisocyanate Aromatic polyisocyanates such as phenyl-4,4'-diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, diphenylmethane-2,4-diisocyanate, and toluene diisocyanate; aliphatic polyisocyanates such as tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, dodecamethylene diisocyanate, and trimethylhexamethylene diisocyanate;Alicyclic polyisocyanates such as 1,3-cyclopentylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, 1,3-di(isocyanatemethyl)cyclohexane, 1,4-di(isocyanatemethyl)cyclohexane, lysine diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 2,4'-dicyclohexylmethane diisocyanate, 2,2'-dicyclohexylmethane diisocyanate, and 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate can be used. These may be used alone or in combination of two or more. Among them, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-diphenylmethane diisocyanate, and toluene diisocyanate are more preferred.;

[0054] In order to control the molecular weight of the resulting polyurethane, a chain terminator having one active hydrogen group may be used as necessary. Examples of these chain terminators include aliphatic monohydroxy compounds having a hydroxyl group, such as methanol, ethanol, propanol, butanol, and hexanol, and aliphatic monoamines having an amino group, such as morpholine, diethylamine, dibutylamine, monoethanolamine, and diethanolamine. These may be used alone or in combination of two or more.

[0055] For the purpose of increasing the heat resistance and strength of the resulting polyurethane, a crosslinking agent having three or more active hydrogen groups or isocyanate groups can be used as necessary.

[0056] The polyurethane according to the present embodiment can be obtained by a known polyurethane manufacturing method. Specifically, for example, a manufacturing method can be mentioned in which a polyol, a polyisocyanate, and the chain extender are charged and reacted. These reactions are preferably carried out at a temperature of 50 to 100°C for 3 to 10 hours. The reaction may also be carried out in an organic solvent.

[0057] Examples of the organic solvent that can be used include ketone solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, methyl ethyl ketone, methyl-n-propyl ketone, acetone, and methyl isobutyl ketone; ester solvents such as methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, isopropyl acetate, isobutyl acetate, isobutyl acetate, and sec-butyl acetate; etc. These organic solvents may be used alone or in combination of two or more.

[0058] The content of the structural units derived from the copolyester of this embodiment in 100% by mass of the polyurethane of this embodiment is preferably 10 to 98% by mass, and more preferably 20 to 98% by mass, which tends to more suitably obtain the effects. In this specification, the content of each structural unit in the polyurethane is measured by NMR.

[0059] The number average molecular weight (Mn) of the polyurethane according to this embodiment may have a lower limit of 5,000 or more, 6,000 or more, 7,000 or more, 8,000 or more, or 10,000 or more, and an upper limit of 1,000,000 or less, 500,000 or less, 100,000 or less, 500,000 or less, or 15,000 or less. Any combination of these upper and lower limits may be used. The number average molecular weight (Mn) of the polyurethane may be 5,000 to 1,000,000, 6,000 to 500,000, 7,000 to 100,000, 8,000 to 500,000, or 10,000 to 15,000. Within the above range, the effect tends to be more favorably obtained.In this specification, the number average molecular weight (Mn) of the polyurethane is a value measured by GPC.

[0060] (Resin composition) Examples of the resin composition of the present embodiment include a thermoplastic resin composition containing the copolyester or polyurethane of the present embodiment described above, and a thermosetting resin composition.

[0061] <Thermoplastic resin composition> When the resin composition of the present embodiment is a thermoplastic resin composition, it may further contain, for example, other resins, a crystallization nucleating agent, a heat stabilizer, a hydrolysis inhibitor, other additives, and the like, as necessary.

[0062] [Crystallization nucleating agent] The crystallization nucleating agent used in the thermoplastic resin composition according to the present embodiment may be any crystallization nucleating agent used in thermoplastic resins derived from biomass resources, such as polylactic acid and polybutylene succinate. For example, talc-based nucleating agents, nucleating agents made of metal salt-based materials having a phenyl group, and nucleating agents made of benzoyl compounds are preferably used. Other known crystallization nucleating agents, such as lactate, benzoate, silica, and phosphate salts, may also be used.

[0063] [Heat stabilizers and hydrolysis inhibitors] The thermoplastic resin composition of the present embodiment preferably contains a phenol-based antioxidant and a phosphite-based antioxidant as a heat stabilizer for the resin composition, and a carbodiimide compound-based hydrolysis inhibitor, such as polycarbodiimide resin (product name: Carbodilite, manufactured by Nisshinbo Chemical Co., Ltd.), as a hydrolysis inhibitor. The heat stabilizer and hydrolysis inhibitor to be added may be one selected from the above three types of additives, but the above two types of heat stabilizers and hydrolysis inhibitors have different functions, and it is preferable that each additive is added together. The amount of heat stabilizer and hydrolysis inhibitor to be added varies depending on the type, but generally, it is preferable that each is about 0.1 to 5 parts by mass per 100 parts by mass of the thermoplastic resin composition.

[0064] [Other additives] It is preferable to further add a silicone-based flame retardant, an organometallic salt-based flame retardant, an organophosphorus-based flame retardant, a metal oxide-based flame retardant, a metal hydroxide-based flame retardant, etc. to the thermoplastic resin composition of this embodiment, which improves the flame retardancy and inhibits the spread of fire, and also improves the fluidity of the biodegradable resin composition, thereby ensuring better moldability.

[0065] A filler can be added to the thermoplastic resin composition of the present embodiment. Examples of the filler include talc, mica, montmorillonite, and kaolin. These fillers act as crystal nuclei to promote crystallization of the copolyester, improving the impact strength and heat resistance of the molded article. In addition, the rigidity of the molded article can be increased.

[0066] The thermoplastic resin composition of the present embodiment may be appropriately blended with various additives such as antioxidants, antiblocking agents, colorants, flame retardants, release agents, antifogging agents, surface wettability improvers, incineration aids, lubricants, dispersion aids, various surfactants, plasticizers, compatibilizers, weather resistance improvers, ultraviolet absorbers, processing aids, antistatic agents, colorants, lubricants, and release agents. As the plasticizer, any known plasticizer generally used as a plasticizer for polymers can be used without particular limitation, and examples thereof include polyester plasticizers, glycerin-based plasticizers, polyvalent carboxylic acid ester-based plasticizers, polyalkylene glycol-based plasticizers, and epoxy-based plasticizers. There are no particular limitations on the compatibilizer as long as it functions as a compatibilizer for copolymer A and copolymer B. Examples of the compatibilizer include inorganic fillers, glycidyl compounds, polymer compounds grafted or copolymerized with acid anhydrides, and organometallic compounds, and one or more of these may be used. By kneading these materials, the heat resistance, bending strength, impact strength, flame retardancy, etc. are improved, which further promotes the application of the materials to molded articles such as housings for electronic devices, such as notebook computers and mobile phones.

[0067] In addition, various fillers known in the art can be blended as the filler. As functional additives, chemical fertilizers, soil conditioners, plant activators, etc. can also be added. The fillers are broadly classified into inorganic fillers and organic fillers. These can be used alone or in a mixture of two or more kinds.

[0068] Examples of inorganic fillers include anhydrous silica, mica, talc, titanium oxide, calcium carbonate, diatomaceous earth, allophane, bentonite, potassium titanate, zeolite, sepiolite, smectite, kaolin, kaolinite, glass, limestone, carbon, wollastonite, calcined perlite, silicates such as calcium silicate and sodium silicate, hydroxides such as aluminum oxide, magnesium carbonate and calcium hydroxide, salts such as ferric carbonate, zinc oxide, iron oxide, aluminum phosphate and barium sulfate, etc. The content of the inorganic filler in the entire composition is usually 1 to 80% by weight, preferably 3 to 70% by weight, and more preferably 5 to 60% by weight. Examples of organic fillers include raw starch, processed starch, pulp, chitin, chitosan, coconut shell powder, wood powder, bamboo powder, bark powder, kenaf powder, straw powder, etc. These can be used alone or in a mixture of two or more. The amount of organic filler added is usually 0.01 to 70% by weight of the total composition.

[0069] The composition can be prepared by any of the conventionally known mixing / kneading techniques. As the mixer, a horizontal cylindrical type, V-shaped type, double cone type mixer, a blender such as a ribbon blender or a super mixer, or various continuous mixers can be used. As the kneader, a batch type kneader such as a roll or an internal mixer, a one-stage type or two-stage type continuous kneader, a twin screw extruder, a single screw extruder, or the like can be used. As the kneading method, a method of adding various additives, fillers, and thermoplastic resins to the heated and melted material and blending them can be mentioned. In addition, a blending oil or the like can be used for the purpose of uniformly dispersing the various additives.

[0070] <Thermosetting resin composition> When the resin composition of the present embodiment is a thermosetting resin composition, it contains, for example, another resin, the copolyester of the present embodiment having reactive groups such as a hydroxyl group or a carboxyl group as a thermosetting resin main component, and further contains a curing agent such as an isocyanate curing agent or a polyamine curing agent that can thermally react with the reactive groups.

[0071] Examples of the curing agent according to the present embodiment include polyisocyanates having an aromatic structure in their molecular structure, such as tolylene diisocyanate, diphenylmethane diisocyanate, polymeric diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, and xylylene diisocyanate, and compounds in which a part of the isocyanate groups of these polyisocyanates is modified with carbodiimide; allophanate compounds derived from these polyisocyanates; polyisocyanates having an alicyclic structure in their molecular structure, such as isophorone diisocyanate, 4,4'-methylenebis(cyclohexylisocyanate), and 1,3-(isocyanatomethyl)cyclohexane; linear aliphatic polyisocyanates, such as 1,6-hexamethylene diisocyanate, lysine diisocyanate, and trimethylhexamethylene diisocyanate, and allophane derivatives thereof. allophanate forms derived from these polyisocyanates; biuret forms derived from these polyisocyanates; trimethylolpropane-modified adducts; polyfunctional isocyanates such as polyisocyanates which are reaction products of the above-mentioned various polyisocyanates with polyol components; polyethylene polyamines such as ethylene diamine, diethylene triamine, triethylene tetramine, tetraethylene pentamine, pentaethylene hexamine, hexaethylene heptamine, heptaethylene octamine, octaethylene nonamine, nonaethylene decamine, piperazine, and N-aminoalkyl piperazines having an alkyl chain with 2 to 6 carbon atoms; and amine compounds such as 3-aminomethyl-3,5,5-trimethylcyclohexylamine (isophorone diamine, or IPDA).

[0072] <Cured product of resin composition> The cured product of the resin composition of the present embodiment is a cured product of the resin composition as the above-mentioned thermoplastic resin composition, or a cured product of the resin composition as the above-mentioned thermosetting resin composition.

[0073] The copolyester in this specification can be used in various applications. Specifically, it can be used in a wide range of applications, such as artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, paints, laminating adhesives, elastic fibers, urethane raw materials, automobile parts, and sporting goods. Since the copolyester of this embodiment, which has excellent biodegradability, is used, the products for the above applications have excellent biodegradability.

[0074] The polyurethanes in this specification can be used in a variety of applications. Specifically, they can be used in a wide range of applications, such as artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, paints, laminating adhesives, vibration-proofing materials, vibration-damping materials, automobile parts, sporting goods, fiber treatment agents, binders, etc. Since the copolyester of this embodiment, which has excellent biodegradability, is used, the products for the above applications have excellent biodegradability.

[0075] The resin composition in the present specification can be used for various applications. Specifically, it can be used for a wide range of applications, such as artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, paints, laminating adhesives, vibration-proofing materials, vibration-damping materials, automobile parts, sporting goods, fiber treatment agents, binders, etc. Since the copolyester of the present embodiment, which has excellent biodegradability, is used, the products for the above applications have excellent biodegradability.

[0076] (Coating agent) The coating agent contains the copolyester of the present embodiment, and further contains other components such as other resins, water, and organic solvents, as necessary.

[0077] The coating agent can be applied to various substrates. An example of the application of the coating agent will be described below. The coating agent is used, for example, for surface coating of the substrate of a food packaging container. Examples of the substrate include plastic films such as styrene-based resin films, polyolefin-based resin films, polyester-based resin films, nylon-based resin films, and laminates thereof. Examples of the substrate include paper, metal-deposited films, aluminum foils, and the like. The coating agent is preferably used for biodegradable substrates. Examples of the biodegradable substrate include paper, polyester-based films, polyolefin-based films, and starch-based films. The coating agent can be used as an ink, an adhesive, or the like.

[0078] (Ink) The ink contains the copolyester of the present embodiment and a colorant, and further contains other components such as a pigment dispersant, water, and an organic solvent, as necessary. The ink is, for example, a printing ink. The ink may be, for example, a water-based ink or an ink that does not contain water (solvent-based ink).

[0079] (glue) The adhesive contains the copolyester of this embodiment, and further contains other components such as other resins, curing agents, and organic solvents, as necessary. The adhesive can also be used as an adhesive composition for lamination, which is laminated onto the various substrates described above to produce composite films used primarily as packaging materials for foods, medicines, detergents, and the like. Such adhesives may be, for example, a two-component curing adhesive containing the copolyester of the present embodiment, a polyester polyol, and a polyisocyanate, or a one-component adhesive made of an acrylic resin, a urethane resin, or an ethylene-vinyl acetate copolymer. As for these adhesives, solvent-based, solventless, aqueous, or alcohol-based adhesives may be used as necessary.

[0080] (Sheet) The sheet is made of a resin composition containing the copolyester of the present embodiment. The resin composition may contain other resins and various additives in addition to the copolyester of the present embodiment. Examples of the various additives include plasticizers, antistatic agents, antioxidants, ultraviolet absorbers, lubricants, antiblocking agents, and heat stabilizers. Examples of the sheet include a non-oriented sheet, a biaxially oriented sheet, and a foamed sheet. The uses of the sheet are not particularly limited, but it can be used in a wide range of applications, such as food packaging containers, construction materials, home electrical appliances, and miscellaneous goods.

[0081] (film) The film is made of a resin composition containing the copolyester of the present embodiment. The resin composition may contain other resins and various additives in addition to the copolyester of the present embodiment. Examples of the various additives include plasticizers, antistatic agents, antioxidants, ultraviolet absorbers, lubricants, antiblocking agents, and heat stabilizers. Examples of the film include unstretched films, biaxially stretched films, and uniaxially stretched films, and can be produced by, for example, melting pellets of the film raw material in an extruder and forming the film into a film using a T-die or inflation method. In the T-die method, a biaxially stretched film is obtained by performing longitudinal stretching using the speed difference between rolls and transverse stretching using a tenter.

[0082] (Laminate) The laminate comprises at least one selected from the sheet and film of the present embodiment, and further comprises other components such as a printed layer and a resin film as necessary. The laminate can be obtained, for example, by laminating a film or sheet to one or both sides of at least one selected from the sheets and films of the present embodiment in order to improve mechanical strength, chemical resistance, etc. Specifically, the laminate can be obtained by thermally laminating a polystyrene-based inflation film to at least one of the front side and back side of the sheet or film, or by laminating an olefin-based film (CPP) using an adhesive. The adhesive used is not particularly limited, and may be, for example, the adhesive of the present embodiment or a known adhesive.

[0083] (Molded body) The molded article can be obtained by molding at least one selected from the sheet, film, and laminate of the present embodiment. The molded article can be obtained, for example, by thermoforming the sheet, film, or laminate of the present embodiment. Examples of the thermoforming method include hot plate contact heat molding, vacuum molding, vacuum pressure molding, and plug assist molding, and in particular, indirect heat molding using an infrared heater as a heat source is preferably used. EXAMPLES

[0084] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto.

[0085] <Measurement of number average molecular weight (Mn) and weight average molecular weight (Mw)> In the examples and comparative examples, the molecular weight of the resin was measured by gel permeation chromatography (GPC) under the following conditions. Measuring equipment: System Controller Waters 600 Controller Liquid delivery pump Waters Model Code 60F RI (Differential Refractometer) Detector Waters 2414 Autosampler Waters 717plus Autosampler

[0086] Data processing: Waters Empower3 Measurement conditions Measurement conditions: Column temperature 40℃ Eluent: Chloroform (CHCl3) Flow rate 1.0ml / min Standard: Polystyrene Column: Shodex GPC LF-G x 1 Shodex GPC LF-804 4 pieces Sample: 100 μl of a chloroform solution containing 0.4% by mass of resin solids filtered through a microfilter

[0087] < 1 H-NMR spectrum measurement Measurement equipment: JEOL RESONANCE "JNM-ECM400S" Magnetic field strength: 400MHz Solvent: Deuterated chloroform Sample concentration: 100mg / 1.0mL

[0088] < 13 C-NMR spectrum> Measurement equipment: JEOL RESONANCE "JNM-ECM400S" Magnetic field strength: 100MHz Solvent: Deuterated chloroform Sample concentration: 100mg / 1.0mL

[0089] <Calculation of 3-hydroxybutyric acid content> 1 The average sequence length was calculated for the peaks in the H-NMR spectrum based on the formula shown below. 3HB content = 3 / 2 x (integral value of 2.8 ppm) / (integral value of 1.2-1.6 ppm)

[0090] <Evaluation of average sequence length> With the above method 13 The C-NMR spectrum of the copolyester of Example 1 was measured. 13 C-NMR spectrum.

[0091] <Evaluation of average sequence length> (Peak assignment) With reference to the following non-patent literature B, 13 The peaks of dyads (combinations of two monomer sequences) on the C-NMR spectrum were assigned. The expression "integral value of a component A-component B dyad" means the integral value of the peak corresponding to component B for adjacent dyads of components A and B.

[0092] [Non-patent document B] Hideki Abe, Yoshiharu Doi, Yoji Hori, Toshimitsu Hagiwara, Physical properties and enzymatic degradability of copolymers of (R)-3-hydroxybutyric acid and (S,S)-lactide, Polymer 1998, 39(1), 59-67.

[0093] (Calculation of average sequence length) The average sequence length of 3HB was calculated based on the formula shown below. Average 3HB chain length = 1 + 2 × (integral value of 3HB dyads at 19.8 ppm) / (integral value of 3HB-lactate dyads at 19.6 ppm + integral value of lactate-3HB dyads at 40.5 ppm)

[0094] <Biodegradability evaluation method> The biodegradability evaluation method was performed with reference to the method described in "2.3. Biodegradation with seawater by BOD method" in the following Non-Patent Document C. The evaluation method in Non-Patent Document C was performed by replacing the inoculum source of JIS K6950 with seawater instead of activated sludge.

[0095] [Non-patent Document C] Atsuyoshi Nakayama*, Naoko Yamano, Norioki Kawasaki, Biodegradation in seawater of aliphatic polyesters, Polymer Degradation and Stability 166 (2019) 290-299.

[0096] [Inoculum source] Seawater collected at Nanko Port, Osaka Prefecture (latitude: 34.634905, longitude: 135.418919) was used as the inoculum source. (Test conditions) Biodegradability measurement method: Soda lime (carbon dioxide absorbent) and a pressure sensor (WTW, OxiTop-IDS (registered trademark)) were attached to a test bottle, and the BOD (biochemical oxygen demand) was measured under the conditions below to calculate the biodegradability. Culture temperature: 27℃, dark place Culture period: 28 days

[0097] [Calculation of biodegradability] The biodegradability of the test materials was calculated based on the following formula: Biodegradation degree (%)=(BOD0-BOD B ) / ThOD×100 BOD0: Biochemical oxygen demand of the test material (measured value: mg) BOD B : Average biochemical oxygen demand in blank test (measured value: mg) ThOD: Theoretical oxygen demand (calculated value: mg) required for the test material to be completely oxidized

[0098] (Synthesis Example 1) "Synthesis of poly(3-hydroxybutyric acid)" In a 100mL three-neck flask equipped with a nitrogen inlet tube, a thermometer, a stirrer, and a Dean-Stark trap, 21.3g (0.205mol) of 3HB, 0.380g (0.00200mol) of p-toluenesulfonic acid, and 40mL of toluene were added, and the mixture was heated at an internal temperature of 95°C for 19 hours. The toluene was distilled off, and 60mL of o-dichlorobenzene was added. The mixture was then reduced pressure to adjust to a reflux state, and further heated to reflux at 95°C for 18 hours. The reaction solution was cooled to room temperature, and 100mL of methanol was added to precipitate a solid, which was then filtered to obtain 12.7g of poly(3-hydroxybutyric acid). The average molecular weight was measured using the method for measuring the average molecular weight described above. The number average molecular weight Mn was 3,400, and the weight average molecular weight Mw was 7,300. The above 1 Using the H-NMR measurement method, 1 The H-NMR spectrum was measured, and the results are as follows: 1H-NMR δ(CDCl3):1.25(m,3H),2.55(m,2H),4.15(m,tr),5.23(m,1H),5.75(d,trace),6.95(m,trace)

[0099] (Synthesis Example 2) "Synthesis of Polylactic Acid (PLA)" 21.2g (0.200mol) of 85% lactic acid and 0.380g (0.00200mol) of p-toluenesulfonic acid were added to a 100mL three-neck flask equipped with a nitrogen inlet tube, a thermometer, a stirrer, and a Dean-Stark trap, and the mixture was heated for 19 hours at an internal temperature of 115°C. Toluene was distilled off, and 100mL of methanol was added to precipitate a solid, which was then filtered to obtain 11.2g of polylactic acid.

[0100] The average molecular weight was measured using the method for measuring the average molecular weight described above. The number average molecular weight Mn was 5,800, and the weight average molecular weight Mw was 11,500.

[0101] The above 1 Using the H-NMR measurement method, 1 The H-NMR spectrum was measured, and the results are as follows: 1 H-NMR δ(CDCl3):1.57(t,3H),4.33(m,trace),4.12(t,1H)

[0102] Example 1 In a test tube equipped with a stirrer and a nitrogen gas inlet tube, 5.20 g (0.0500 mol) of 3-hydroxybutyric acid, 52 mL of toluene, and 0.475 g (0.00250 mol) of p-toluenesulfonic acid were charged, and polymerization was carried out at 95° C. for 4 hours while removing water. 21.1 g (0.199 mol) of 85% lactic acid aqueous solution was added to the test tube containing poly(3-hydroxybutyric acid), and the reaction was carried out at 115° C. for 52 hours while removing water. The reaction liquid was cooled to room temperature, and 100 mL of methanol was added to precipitate a solid, which was then filtered to obtain a 3-hydroxybutyric acid-lactic acid copolyester as the copolyester of this embodiment. The average molecular weight was measured using the method for measuring the average molecular weight described above. The number average molecular weight Mn was 7,100, and the weight average molecular weight Mw was 10,100.

[0103] The content of the structure derived from 3-hydroxybutyric acid was measured by the method described above in <Calculation of the content of 3-hydroxybutyric acid>. The results are shown in Table 1. The average sequence length of the structures derived from 3-hydroxybutyric acid was measured by the method described above in <Evaluation of average sequence length>. The results are shown in Table 1. The biodegradability was evaluated by the method described above in <Biodegradability Evaluation>. The results are shown in Table 1.

[0104] Example 2 In a test tube equipped with a stirrer and a nitrogen gas inlet tube, 5.20 g (0.0500 mol) of 3-hydroxybutyric acid, 52 mL of toluene, and 0.475 g (0.00250 mol) of p-toluenesulfonic acid were charged, and polymerization was performed at 95 ° C. for 22 hours while removing water. 21.1 g (0.199 mol) of 85% lactic acid aqueous solution was added to the test tube containing poly(3-hydroxybutyric acid), and the reaction was performed at 115 ° C. for 33 hours while removing water. The reaction liquid was cooled to room temperature, and 100 mL of methanol was added to precipitate a solid, and filtration was performed to obtain a 3-hydroxybutyric acid-lactic acid copolyester as the copolyester of this embodiment. The average molecular weight was measured using the method for measuring the average molecular weight described above. The number average molecular weight Mn was 6,900, and the weight average molecular weight Mw was 9,000. The content, average chain length, and biodegradability of 3-hydroxybutyric acid were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0105] Example 3 In a test tube equipped with a stirrer and a nitrogen gas inlet tube, 2.08 g (0.0200 mol) of 3-hydroxybutyric acid, 46 mL of toluene, and 0.380 g (0.00200 mol) of p-toluenesulfonic acid were charged, and polymerization was performed at 95 ° C. for 5 hours while removing water. 19.1 g (0.180 mol) of 85% lactic acid aqueous solution was added to a test tube containing poly(3-hydroxybutyric acid), and the reaction was performed at 115 ° C. for 33 hours while removing water. The reaction liquid was cooled to room temperature, and 100 mL of methanol was added to precipitate a solid, and filtration was performed to obtain a 3-hydroxybutyric acid-lactic acid copolyester as the copolyester of this embodiment. The average molecular weight was measured using the method for measuring the average molecular weight described above. The number average molecular weight Mn was 6,900, and the weight average molecular weight Mw was 12,000. The content, average chain length, and biodegradability of 3-hydroxybutyric acid were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0106] Example 4 In a test tube equipped with a stirrer and a nitrogen gas inlet tube, 2.08 g (0.0200 mol) of 3-hydroxybutyric acid, 43 mL of toluene, and 0.380 g (0.00200 mol) of p-toluenesulfonic acid were charged, and polymerization was performed at 95 ° C. for 10 hours while removing water. 19.1 g (0.180 mol) of 85% lactic acid aqueous solution was added to a test tube containing poly(3-hydroxybutyric acid), and the reaction was performed at 115 ° C. for 33 hours while removing water. The reaction liquid was cooled to room temperature, and 100 mL of methanol was added to precipitate a solid, and filtration was performed to obtain a 3-hydroxybutyric acid-lactic acid copolyester as the copolyester of this embodiment. The average molecular weight was measured using the method for measuring the average molecular weight described above. The number average molecular weight Mn was 7,000, and the weight average molecular weight Mw was 11,000. The content, average chain length, and biodegradability of 3-hydroxybutyric acid were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0107] Comparative Example 1 In a test tube equipped with a stirrer and a nitrogen gas inlet tube, 2.60 g (0.0250 mol) of 3-hydroxybutyric acid, 28.3 g (0.267 mol) of 85% lactic acid aqueous solution, 53 mL of toluene, and 0.475 g (0.00250 mol) of p-toluenesulfonic acid were charged, and the mixture was reacted at 115°C for 24 hours while removing water, and then the toluene was distilled off and the mixture was polymerized at 140°C for 10 hours under reduced pressure. The reaction solution was cooled to room temperature, 100 mL of methanol was added, and the mixture was filtered to obtain a copolyester of 3-hydroxybutyric acid-lactic acid. The average molecular weight was measured using the method for measuring the average molecular weight described above. The number average molecular weight Mn was 9,800, and the weight average molecular weight Mw was 19,500. The content, average chain length, and biodegradability of 3-hydroxybutyric acid were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0108] Comparative Example 2 In a test tube equipped with a stirrer and a nitrogen gas inlet tube, 5.20 g (0.0500 mol) of 3-hydroxybutyric acid, 15.90 g (0.150 mol) of 85% lactic acid aqueous solution, 52 mL of toluene, and 0.380 g (0.00200 mol) of p-toluenesulfonic acid were charged, and the mixture was reacted at 115 ° C for 24 hours while removing water, and then the toluene was distilled off and the mixture was polymerized at 140 ° C for 10 hours under reduced pressure. The reaction solution was cooled to room temperature, 100 mL of methanol was added, and the mixture was filtered to obtain a copolyester of 3-hydroxybutyric acid-lactic acid. The average molecular weight was measured using the method for measuring the average molecular weight described above. The number average molecular weight Mn was 6,100, and the weight average molecular weight Mw was 11,500. The content, average chain length, and biodegradability of 3-hydroxybutyric acid were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0109] [Table 1]

[0110] (Consideration) When highly biodegradable 3-hydroxybutyric acid-derived structures are arranged in a copolyester with a specific average chain length, the 3-hydroxybutyric acid-derived building blocks are cleaved by enzymes secreted by microorganisms in the environment, converting the copolyester into oligomers that can be metabolized by microorganisms, and the entire copolyester is biodegraded. [Industrial Applicability]

[0111] The copolyester of this embodiment has a structure derived from 3-hydroxybutyric acid and exhibits biodegradability, and therefore, a resin composition containing the copolyester of this embodiment is expected to be used in various applications such as sustainable products (packaging materials, films).

Claims

1. The copolyester has a structural unit (3HB-U) derived from 3-hydroxybutyric acid (3HB) and a structural unit (HA-U) derived from hydroxyalkanoic acid (HA), The hydroxyalkanoic acid (HA) is lactic acid, the content of the structural unit (3HB-U) derived from 3-hydroxybutyric acid (3HB) is 1 to 40 mol% relative to 100 mol of all structural units of the copolyester, The copolyester is characterized in that the average sequence length of the structural units (3HB-U) derived from 3-hydroxybutyric acid (3HB) in the copolyester is 5 to 8.

2. 2. The copolyester of claim 1 which is the reaction product of poly(3-hydroxybutyric acid) (PHB) with said hydroxyalkanoic acid (HA) or said polyester of hydroxyalkanoic acid (HA) (PHA).

3. 3. The copolyester of claim 2, wherein the number average molecular weight of the polyester of hydroxyalkanoic acid (HA) (PHA) is from 1,000 to 500,000.

4. A process for producing the copolyester according to any one of claims 1 to 3, comprising the steps of: A method for producing a copolyester, comprising the step of reacting poly(3-hydroxybutyric acid) (PHB), which is a polyester of 3-hydroxybutyric acid (3HB), with the hydroxyalkanoic acid (HA) or a polyester of hydroxyalkanoic acid (HA) (PHA).

5. A resin composition comprising the copolyester according to any one of claims 1 to 3.

6. A sheet or film comprising the resin composition according to claim 5.

Citation Information

Patent Citations

  • Copolymer resin composition, molded article, and method of producing the copolymer resin composition

    JP2012087207A

  • Block copolymer and resin composition containing the same, and method for producing block copolymer

    JP2018109103A

  • Poly(beta-methyl-delta-valerolactone) block polymers

    US20170044326A1